Imbalance of the reciprocally inhibitory loop between the ubiquitin-specific protease USP43 and EGFR/PI3K/AKT drives breast carcinogenesis. Issue 9 (September 2018) - He, Lin; Liu, Xinhua; Yang, Jianguo; Li, Wanjin; Liu, Shumeng; Liu, Xujun; Yang, Ziran; Ren, Jie; Wang, Yue; Shan, Lin; Guan, Chengjian; Pei, Fei; et al.
Abstract Hyperactivation of EGFR/PI3K/AKT is a prominent feature of various human cancers. Thus, understanding how this molecular cascade is balanced is of great importance. We report here that the ubiquitin-specific protease USP43 is physically associated with the chromatin remodeling NuRD complex and catalyzes H2BK120 deubiquitination. Functionally this coordinates the NuRD complex to repress a cohort of genes, includingEGFR, which are critically involved in cell proliferation and carcinogenesis. We show that USP43 strongly suppresses the growth and metastasis of breast cancer in vivo. Interestingly, USP43 also exists in the cytoplasm, where it is phosphorylated by AKT, enabling its binding to the 14-3-3β/ε heterodimer and sequestration in the cytoplasm. Significantly, hyperactivation of EGFR/PI3K/AKT in breast cancer is associated with the cytoplasmic retention of USP43 and thus, the inhibition of its transcriptional regulatory function. Moreover, cancer-associated mutations ofUSP43 affect its subcellular localization and/or epigenetic regulatory functions. Nuclear USP43 is significantly reduced in breast carcinomas and is associated with EGFR accumulation and AKT hyperactivation. A low level of nuclear USP43 correlates with higher histologic grades and poor prognosis. Our study identifies USP43 to be an H2BK120 deubiquitinase and a potential tumor suppressor and reveals a reciprocally inhibitory loop between USP43 and EGFR/PI3K/AKT, whose imbalance drives breast carcinogenesis.